2011
DOI: 10.1016/j.bbmt.2010.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and Red Blood Cell Utilization and Transfusion Independence in Umbilical Cord Blood and Allogeneic Peripheral Blood Hematopoietic Cell Transplants

Abstract: Allogeneic hematopoietic cell transplantation (HCT) recipients have substantial transfusion requirements. Factors associated with increased transfusions and the extent of blood product use in umbilical cord blood (UCB) recipients are uncertain. We reviewed blood product use in 229 consecutive adult recipients of allogeneic HCT at the University of Minnesota: 147 with leukemia, 82 lymphoma or myeloma; 58% received unrelated UCB and 43% sibling donor peripheral blood stem cell (PBSC) grafts. Although neutrophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 25 publications
5
49
1
Order By: Relevance
“…We restricted our analysis to first transplants because second transplants have of themselves been associated with increased frequency and duration of transfusion need. 7 Our data showed that time to platelet engraftment was significantly influenced by graft type, donor type and intensity of conditioning regimes. That time to platelet engraftment was influenced by graft type and donor type has been previously reported, with PBSC grafts associated with faster platelet engraftment.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…We restricted our analysis to first transplants because second transplants have of themselves been associated with increased frequency and duration of transfusion need. 7 Our data showed that time to platelet engraftment was significantly influenced by graft type, donor type and intensity of conditioning regimes. That time to platelet engraftment was influenced by graft type and donor type has been previously reported, with PBSC grafts associated with faster platelet engraftment.…”
Section: Discussionmentioning
confidence: 84%
“…Time to platelet independence in one large series of cord blood transplants was 41 versus 14 days for PBSC grafts in other allogeneic transplants and 25 vs 13 days for red cell transfusion independence. 7 In this series, cord blood transplant recipients also required more RBC and platelet transfusions than did recipients of other graft types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In general, engraftment time is shortest with HPC-A and greatest when HPC-C is used 6 ; however, considerable patient-to-patient variability exists. One study that compared HPC-C and HPC-A noted roughly equivalent neutrophil recovery times but found a longer time to platelet and RBC engraftment for HPC-C. 5 These prolonged engraftment times translated into higher transfusion rates for RBCs and platelets.…”
Section: Introductionmentioning
confidence: 99%
“…3 RBC engraftment is more difficult to assess and may be defined by the appearance of 1% reticulocytes in the peripheral blood, 4 or, on the day of the last RBC transfusion, with no transfusion given the following 30 days. 5 Typically, neutrophil engraftment is defined as an absolute neutrophil count of more than 500/µL across 3 consecutive days. 3 Engraftment is influenced by many factors, including the relationship of the donor to the patient, the stem cell source, and the dose of CD34 + cells in the transplantation.…”
Section: Introductionmentioning
confidence: 99%